Deploying time investigation of automotive active hood lift mechanism with different design parameters of hinge part - Tae-Hoon Lee; Gun-Ha Yoon; Seung-Bok Choi (Advances in Mechanical Engineering, 2016)
This article investigates the change in deploying time of an active hood lift mechanism of a passenger vehicle activated by a gunpowder actuator. Especially, in this work, the deploying time is investigated by changing the principal design parameters of the hinge part of the hood mechanism. After briefly introducing the working principle of the active hood lift mechanism operated by the gunpowder actuator, the governing dynamic equations of the active hood lift mechanism are formulated for deploying motion. Subsequently, using the governing equations of motion, the response time for deploying the hood lift mechanism is investigated by changing several geometric locations such as the location of actuator. Then, a comparison is made of the total response time to completely deploy the hood lift mechanism with the existing conventional hood lift mechanism and the proposed active hood lift mechanism. In addition, the workable driving speed of the proposed active hood lift mechanism is compared with the conventional one by changing the powder volume of the actuator.